Effects of adding tocotrienol-tocopherol mixed fraction and vitamin C supplementation on coronary risk biomarkers in patients with hypercholesterolaemia with moderate coronary risk - Muhamed T. Osman, Azlina Abdul Razak, Huzaimi Haron, Thuhairah Rahman & , Suhaila Muid, Tengku Saifudin Tengku Ismail, Anis Safura Ramli & , Sushil Kumar Vasudevan & , Hapizah Nawawi & (Journal of Applied Pharmaceutical Science, 2016)
This study was a prospective clinical trial to investigate the effects of adding combined tocotrienol-tocopherol mixed fraction (TTMF) and vitamin C (TTMF+C) supplementation on coronary biomarkers in non-statin and statin treated patients with hypercholesterolaemia (HC) with moderate coronary risk. A total of 35 patients were randomised at baseline into one of two groups, (G1) TTMF+C (320mg TTMF plus 500mg vitamin C) alone daily and (G2) TTMF+C (320mg TTMF plus 500mg vitamin C) plus atorvastatin 10 mg daily. The entire supplementation were taken for 12 months. Fasting serum samples were taken at baseline, 2weeks, 3months, 6months and 12months post-randomisation and analysed for inflammatory biomarkers; high sensitivity C- reactive protein (hsCRP) and interleukin-6 (IL6). Combination of TTMF and vitamin C supplementation leads to neutral effects on lipid profiles and inflammation; with no added benefit in statin-treated HC patients with moderate coronary risk. This neutral effects may be attributed to the tocopherol composition in TTMF which could possibly attenuate any potential beneficial effects of tocotrienols. Clinical studies using pure tocotrienols in the absence of tocopherols would further confirm this.
Keywords: Hypercholesterolaemia, Tocopherol-Tocotrienol mixed fraction vitamin E, Vitamin C, Moderate Coronary Risk, Antioxidants.